2017
DOI: 10.1002/dneu.22549
|View full text |Cite
|
Sign up to set email alerts
|

α2‐glycine receptors modulate adult hippocampal neurogenesis and spatial memory

Abstract: The α2-glycine receptors (GlyRs) play important roles during early central nervous system development. However, these receptors' possible involvement in neurodevelopmental events occurring in the adult brain remains to be explored. Adult hippocampal neurogenesis (AHN) is the process by which new granule cell neurons are added to the dentate gyrus (DG) throughout adulthood. In this study, we observed that hippocampal adult neural stem cells (ANSCs) express α2-containing GlyRs. Pharmacological inhibition of GlyR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…Open‐field assays did not show differences between genotypes in total distance travelled or time spent in the centre, which is in agreement with previously published data (Blednov et al, 2015; Lin et al, 2017;Molchanova et al, 2018 ; Pilorge et al, 2016). However, we detected changes in motor learning skills using the accelerating rotarod that showed an increased latency to fall in both male and female Glra2 KO mice.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Open‐field assays did not show differences between genotypes in total distance travelled or time spent in the centre, which is in agreement with previously published data (Blednov et al, 2015; Lin et al, 2017;Molchanova et al, 2018 ; Pilorge et al, 2016). However, we detected changes in motor learning skills using the accelerating rotarod that showed an increased latency to fall in both male and female Glra2 KO mice.…”
Section: Discussionsupporting
confidence: 92%
“…Alteration in glutamatergic transmission, cortical synaptic plasticity (Morelli et al, 2017) and impaired motor memory consolidation were also detected in this mouse (Molchanova et al, 2018) suggesting the presence of compensatory mechanisms. On the other hand, using another model of Glra2 KO mice, it was shown that this mouse displayed impaired adult hippocampal neurogenesis and deficits in spatial memory (Lin et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another report, deletions including DIP2C and/or ZMYND11 were identified in several patients with developmental delay including three patients with seizures (DeScipio et al, 2012). GLRA2 is a glycine receptor involved in neurodevelopment in which mutations are implicated in autism, (Pilorge et al, 2016;Lin et al, 2017) including a patient with comorbid epilepsy (Zhang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In another report, deletions including DIP2C and/or ZMYND11 were identified in several patients with developmental delay including three patients with seizures (DeScipio et al, 2012). GLRA2 is a glycine receptor involved in neurodevelopment in which variants are implicated in autism (Pilorge et al, 2016;Lin et al, 2017), including a patient with comorbid epilepsy (Zhang et al, 2017).…”
Section: Geneticsmentioning
confidence: 99%